2002
DOI: 10.1021/ja027809r
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Mechanistic Dichotomy in the Cyclization of 1-(2-Ethynylphenyl)-3,3-dialkyltriazenes:  Competition between Pericyclic and Pseudocoarctate Pathways

Abstract: The mechanistic aspects of the cyclization of (2-ethynylphenyl)triazenes under both thermal and copper-mediated conditions are reported. For cyclization to an isoindazole, a carbene mechanistic pathway is proposed. The carbene intermediate can react with oxygen, dimerize to give an alkene, or be trapped either intermolecularly (using 2,3-dimethyl-2-butene to generate a cyclopropane) or intramolecularly (using a biphenyl moiety at the terminus of the acetylene to form a fluorene). Density-functional theory (DFT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 113 publications
(83 citation statements)
references
References 55 publications
2
81
0
Order By: Relevance
“…Some examples have demonstrated the applicability of this method to distinguishing between pericyclic/pseudopericyclic and coarctate/pseudocoarctate reactivity. [3,5,26,27,29] Figure 5 presents the ACID isosurface of the reactant, product and transition state for this reaction at an isosurface value of 0.05 au. Current density vectors are plotted Figure 5.…”
Section: Acid (Anisotropy Of the Current-induced Density) Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some examples have demonstrated the applicability of this method to distinguishing between pericyclic/pseudopericyclic and coarctate/pseudocoarctate reactivity. [3,5,26,27,29] Figure 5 presents the ACID isosurface of the reactant, product and transition state for this reaction at an isosurface value of 0.05 au. Current density vectors are plotted Figure 5.…”
Section: Acid (Anisotropy Of the Current-induced Density) Methodsmentioning
confidence: 99%
“…[25] Birney [15] found that disconnections can also occur in coarctate reactions, similarly to pseudopericyclic reactions. Kimball et al [26] have termed these reactions pseudocoarctate.…”
Section: Introductionmentioning
confidence: 99%
“…2a shows the ACID isosurface for the 5-membered ring cyclization to the isoindazole. 37 As a reference, the transition state for the all-carbon analogue is shown in Fig. 2b.…”
Section: Acid Calculationsmentioning
confidence: 99%
“…The subsequent mechanism of Et 2 N-loss as the corresponding imine took us a great deal of additional experimental and computational effort to figure out; however, because the focus of this article is on coarctate reactions, we refer the reader to the full paper that lays out the cinnoline mechanistic case in greater detail. 37 …”
Section: Cinnoline Formation Via Zwitterionsmentioning
confidence: 99%
See 1 more Smart Citation